FEATURES OF TRANSFER PHENOMENA IN POLYCRYSTALLINE FILM STRUCTURES - Yusupova Dilfuza Aminovna (Scholars Digest Publishing, 2023)
The paper substantiates a physical approach to describing transport phenomena in polycrystalline semiconductor films. The case including the transfer of charge carriers across block boundaries (BB) is considered. The electrical conductivities of the barrier are found in the directions along the axes (perpendicular to the BB) and (parallel to the BB).
Keywords: Transport phenomena, polycrystalline semiconductor films, intergranular barriers, elementary unit of a crystal, dislocations, crystal, diffusion, minimum crystal, a block boundary, a boundaries of crystallites, electrical conductivity of the barrier, anisotropy of conductivity, electrical conductivity of a polycrystalline film, mean free path.